SPATIAL AND TEMPORAL PATTERNS OF CLIMATIC CHANGE IN THE SOKOTO-RIMA RIVER BASIN, SUDANO-SAHEL REGION, NIGERIA - Ezemonye Mary .N; Emeribe Chukwudi .N (European Scientific Journal, ESJ, 2015)
The Sokoto-Rima drainage basin is important for food and agricultural production in the country as well as has a sizeable number of irrigation and other river basin development projects that requires the knowledge of response patterns of climatic variables to changing climate in terms of the magnitude of change, rate of change, spatial and temporal trends of the changing climate both annual and seasonal, when the change became significant. Such information is very useful in designing measures and formulating policy for appropriate response and adaptation to climate change. The study therefore attempts to investigate the response of rainfall and temperature to climatic change. To achieve this aim, data from the Nigerian Meteorological Agency, NIMET and the global Climatic Research Unit CRU for the period 1943-2012 were obtained and utilizing various statistical methods such as Mann-Kendel, Spearman’s Rho, Linear regression, free distribution CUSUM, cumulative deviation and Worsley Likelihood tests the data were tested for trends and step jumps. The Pearson’s Product correction was performed to ascertain the reliability of CRU data used in the study. The results revealed evidence of decreasing tend in the time series of annual rainfall, while evidence of rising trend was detected in the time series of temperature. There was evidence of statistical difference between the two climatic periods; 1943-1977 and 1978-2012. These were detected at statistical thresholds of α<0.05 for rainfall and α<0.01 for temperature. Average percentages of change in annual rainfall and temperature which is the magnitude of deviation from annual rainfall and temperature of the first climatic period during the second climatic period were determined as 5.7% (rainfall) and 0.95% (temperature) in the northwest part of the study area, 3.2% (rainfall) and 0.88 (temperature) in southwest of the study area, 5.99% (rainfall) and 1.02% (temperature) in northeast of the study area , 2.3% (rainfall) and 0.87% (temperature) southeast of the study area. On a seasonal scale, average percentages of change in rainfall northwest of the study area were observed as 8.5%, 6.6% in southwest, 13.0% in northeast and 3.2% southeast of the study area. The study showed that annual temperature change in the Sokoto-Rima River basin was observed to be higher than the observed 0.74 ± 0.18°C increase in average global temperature of the Earth during the past 100 years. Change points in the long-term rainfall annual distributions occurred in1970, while change point in long-term annual temperature pattern in the basin was observed in 1981.